Onchocerca takaokai n. sp. (Nematoda: Filarioidea) in Japanese wild boars (Sus scrofa leucomystax): Description and molecular identification of intradermal females. Issue 6 (December 2015) - Uni, Shigehiko; Fukuda, Masako; Agatsuma, Takeshi; Bain, Odile; Otsuka, Yasushi; Nakatani, Jun; Matsubayashi, Makoto; Harada, Masashi; Omar, Hasmahzaiti; Ramli, Rosli; Hashim, Rosli; Azirun, Mohd Sofian; et al.
Abstract Human zoonotic onchocercosis is caused by Onchocerca dewittei japonica, parasitic in wild boars (Sus scrofa leucomystax) in Japan. Previously, microfilariae longer than those of Onchocerca dewittei japonica were observed in skin snips from wild boars during the study of O. dewittei japonica. Moreover, the third-stage larvae (L3) of these longer microfilariae were obtained from the blackfly Simulium bidentatum after experimental injections. Based on morphometric and molecular studies, similar L3 were found in blackflies during fieldwork in Oita, Japan. However, except for O. dewittei japonica, adult worms of Onchocerca have not been found in wild boars. In this study, we discovered adult females of a novel Onchocerca species in the skin of a wild boar in Oita, and named it Onchocerca takaokai n. sp. Females of this new species had longer microfilariae and differed from O. dewittei japonica in terms of their morphological characteristics and parasitic location. The molecular characteristics of the cytochrome c oxidase subunit 1 and 12S rRNA genes of the new species were identical to those of the longer microfilariae and L3 previously detected, but they differed from those of O. dewittei japonica at the species level. However, both species indicated a close affinity among their congeners and Onchocerca ramachandrini, parasitic in the warthog in Africa, was basal in the Suidae cluster of the 12S rRNA tree.